Challenge of Strengthening the Health of Older Employees in the Workplace to Improve Job Longevity - P. I. Ananchenkova; E. V. Vashalomidze; Y. G. Egiazarov (Здоровье мегаполиса, 2024)
Introduction. Older workers are more likely to face health problems. This issue is becoming more important in the context of the trend towards prolonged working life. Given the significant amount of time spent in the workplace, the better health of older workers is crucial for their continued employment.The purpose was to conduct a literature review of studies discussing the problem of health preservation of older workers in the workplace as a factor ensuring prolonged working life and job longevity.Materials and methods. In our study, the methods of content analysis of scientific literature on the health of older workers, corporate programs promoting health-saving practices, and the creation of healthy workplaces were used. In addition, a secondary analysis of data obtained from a study conducted by the Age-Friendly non-profit organization in 2022 in the USA was presented.Results. The physical health of older workers significantly differs from younger staff. This issue requires a search for special approaches to labor protection and health-saving conditions in the workplace. Recent studies on workforce aging have shown that older workers are characterized by objective age-related physical changes, which reduce their activity, productivity, and efficiency as a labor resource. Corporate programs on employee health and the promotion of healthy job longevity should be aimed at providing comprehensive health education, creating a working environment that promotes  health  improvement  by  both  physical and social means, elaborating corporate culture emphasizing the value of health and longevity, as well as enabling systemic conditions for regular medical examinations, stress testing, relaxation, and rehabilitation of employees after a hard workday.